Trending topics of SIRT1 in tumorigenicity - Garcia-Peterson, Liz M.; Li, Xiaoling (Biochimica et biophysica acta. General subjects, 2021)
Carcinogenesis is governed by a series of genetic alterations and epigenetic changes that lead to aberrant patterns in neoplastic cells. Sirtuin-1(SIRT1), an NAD+-dependent protein deacetylase, is capable of deacetylating histones and non-histone substrates that regulate various physiological activities during tumorigenesis. Recent studies have identified the role of SIRT1 in different stages of cancer, including genome instability, tumor initiation, proliferation, metabolism, and therapeutic response. However, the action of SIRT1 has been reported to be both oncogenic and tumor suppressive during carcinogenesis. Consequently, the biological functions of SIRT1 in cancer remain controversial. We highlight the most recent findings on SIRT1 in different stages of tumorigenesis, and update the current status of SIRT1 small molecule modulators in clinical application of cancer treatment. By targeting both tumor suppressors and oncogenic proteins, SIRT1 has a bifunctional role at different stages of tumorigenesis. The impact of SIRT1 on tumorigenesis is also distinct at different stages and is dependent on its dosages. SIRT1 suppresses tumor initiation through its functions in promoting DNA repair, increasing genome stability, and inhibiting inflammation at the pre-cancer stage. However, SIRT1 enhances tumor proliferation, survival, and drug resistance through its roles in anti-apoptosis, pro-tumor metabolism, and anti-inflammation (inhibition of anti-tumor immunity) at the stages of tumor progression, metastasis, and relapse. Consequently, both SIRT1 inhibitors and activators have been explored for cancer treatment. Better understanding the dose- and stage-dependent roles of SIRT1 in each cancer type can provide new avenues of exploration for therapy development. •SIRT1 is an NAD+-dependent HDAC important for epigenetics, metabolism, and aging.•SIRT1 has a bifunctional role in tumorigenesis.•The impact of SIRT1 on tumorigenesis is distinct at different stages.•Both SIRT1 inhibitors and activators are under exploration for cancer treatment.